2019
DOI: 10.1186/s12870-019-1970-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative omics analysis on phytohormones involved in oil palm seed germination

Abstract: Background Heat treatment is widely used to break dormancy for seed germination and phytohormones could be deeply involved. However, effect of heat treatment on phytohormone related genes/proteins/metabolites and possible relationship with dormancy release remains unclear in oil palm. In this study, oil palm seeds were heat-treated at 39 °C for 60 days according to the method for commercial production. The embryos of seeds during heat treatment (0 d, 15 d, 30 d, 45 d and 60 d) and of germinated se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…As such, α-tocopherol is probably an important actor to down-regulate lipid peroxidation at the very first steps of palm seed germination, just after imbibition. In fact, across different palm species, just after imbibition, there is a peak in H 2 O 2 that seems to coincide with that in JA and α-tocopherol content [ 35 , 51 , 52 ].…”
Section: Ros Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, α-tocopherol is probably an important actor to down-regulate lipid peroxidation at the very first steps of palm seed germination, just after imbibition. In fact, across different palm species, just after imbibition, there is a peak in H 2 O 2 that seems to coincide with that in JA and α-tocopherol content [ 35 , 51 , 52 ].…”
Section: Ros Metabolismmentioning
confidence: 99%
“…Hormonal profiling of germinating oil palm seeds has shown that several hormones vary in the first days, not only gibberellins, which only show a small increase [ 65 ]. The most visible events are a strong decrease in abscissic acid and a modest increase in auxin [ 52 , 66 ]. The decrease in abscissic acid (and its antagonism with gibberellins) is not surprising, since it is an essential component of dormancy breaking in mixed physical-physiological dormant seeds [ 53 , 67 ].…”
Section: Control Of Germinationmentioning
confidence: 99%
“…However, the effect of heat treatment on phytohormone-related genes/ proteins/metabolites and possible relationship with dormancy release is not well understood. Wang et al (2019) carried out integrative omics analysis on the phytohormones involved in oil palm seed germination under conditions used for commercial production to discover the mechanisms involved in oil palm seed germination. Differentially expressed genes and proteins (DEG and DEP) related to seed germination were identified using RNA-seq and isobaric tags for relative and absolute quantitation (iTRAQ) and the results validated with qPCR and western blot.…”
Section: Integrative Omics For Understanding Oil Palm Seed Germinationmentioning
confidence: 99%
“…The concentration of the endogenous phytohormones involving gibberellin A1 (GA 1 ), gibberellin A3 (GA 3 ), gibberellins A4 (GA 4 ), cytokinin (CTK), abscisic acid (ABA), indole-3-acetic acid (IAA) during seed germination was determined by LC-MS/MS system (Qin et al, 2019;Wang et al, 2019) with slight modifications. Each sample was transferred into a 2 mL LC/MS glass vial for LC-MS/ MS analysis.…”
Section: Determination Of Phytohormone Contentmentioning
confidence: 99%